Dacomitinib, an Irreversible Pan-ErbB Inhibitor Significantly Abrogates Growth in Head and Neck Cancer Models That Exhibit Low Response to Cetuximab - Ather, Ferdows; Hamidi, Habib; Fejzo, Marlena S.; Letrent, Stephen; Finn, Richard S.; Kabbinavar, Fairooz; Head, Christian; Wong, Steven G. (PLOS ONE, 2013)
Aberrant epidermal growth factor (EGF) signaling is associated with tumor growth in squamous cell carcinoma of the head and neck in humans (HNSCC), and is a major focus of targeted therapy. Cetuximab, a monoclonal antibody against EGFR, has been successful at prolonging survival but has only a 10% tumor shrinkage response rate in a clinical setting. The goal of this study was to compare dacomitinib (PF-00299804), a next generation small molecule tyrosine kinase inhibitor that irreversibly blocks multiple HER family receptors (HER-1 (EGFR), HER-2 and HER-4 tyrosine kinases), to cetuximab, the current FDA approved anti-EGFR medication for HNSCC and erlotinib, an EGFR specific small molecule tyrosine kinase inhibitor. Dacomitinib, erlotinib and cetuximab were tested in a panel of 27 HNSCC cell lines. Treatment with 100 ug/ml of cetuximab or 1 uM of erlotinib inhibited growth by at least 50% in 7/27 cell lines, while treatment with 1 uM of dacomitinib had similar growth inhibition in 17/27 lines. Cell lines representing three levels of sensitivity to dacomitinib were further examined using Western blots, cell cycle and apoptosis analysis. Treatment with 100 nM of dacomitinib reduced EGFR activity and downstream AKT and ERK pathways more effectively than treatment with 100 ug/ml of cetuximab in all ten tested lines. Although both compounds induced apoptosis at similar levels, dacomitinib caused greater G0/G1 arrest. Sensitivity to EGFR blockade was associated with levels of EGFR and ERK and was not associated with common oncogenic mutations and copy number variations. Phosphorylated and total EGFR and ERK levels correlate with sensitivity to both cetuximab and dacomitinib. Three of the four lines in the exquisitely sensitive group had the highest levels of phosphorylated and total EGFR and ERK among the ten lines selected, while the three resistant lines collectively had the lowest levels. Neither pAKT nor tAKT was associated with sensitivity.